Efektivitas Ekstrak Daun Jambu Biji (Psidium Guajava l.) Sebagai Inhibitor Pada Baja Karbon St37 dalam Medium Korosif NaCl 3% - Dian Mardiana; Ediman Ginting; Agus Riyanto (Journal of Energy, Material, and Instrumentation Technology, 2020)
The effectiveness of guava leaf extract as an inhibitor of St37 carbon steel in a corrosive medium of 3% NaCl had been researched. The concentration of guava leaf extract inhibitor was used 0%. 3%. 5% and 7% with immersion time of 4 and 8 days. Corrosion rate testing was done by weight loss method. The results of the research at each immersion time, showed that the optimum concentration of leaf guava extract to inhibit corrosion is 7% and the longer time immersion resulted in decreasing corrosion rate on St37 carbon steel. The maximum effectiveness of inhibitor occurred at 7% concentration with 8 days immersion time which is 70,12%. Characterization using Scanning Electron Microscopy (SEM) in sample St37-4-7 and St37-8-7 not all surfaces corroded, but on samples St37-4-0 and St37-8-0 almost all samples were corroded. This is reinforced with eds results in which sample St37-8-0 and St37-4-0 have a lower FeO content than sample St37-8-7 and St37-4-7. The X-Ray Diffraction (XRD) result shows that the phase was Fe.